Exploring How English Teachers Accommodate Students’ Learning Style in the 21st Century: A Survey - Yanti, Novi; Arrasyid, Farouk Imam; Noerjanah, Siti Luruh Ayu (STIT Buntet Pesantren Cirebon, 2023)
The aim of this descriptive qualitative research is to explore how English teachers accommodate students’ learning styles in 21st century, to find out students’ learning style and how English teachers’ accommodate it based on students’ perspective. The procedure applied in this qualitative research are data collection, data presentation, conclusion drawing and verification. The data collection techniques used were questionnaire, interview and observation. There are still few researchers who examine on how English teachers accommodate students’ learning style based on students’ perspective. As final note, teachers need to recognize their students’ different learning styles and prepare the appropriate methods to deliver the subject matters. In addition, learning style is the way a person takes in, understands, expresses and remembers information. As a result, teaching and learning process will be very interactive and effective by recognizing students’ different learning style and the way to accommodate it appropriately.